Re-Creating an Alpine Way of Life: Tyrolean Settlers in the Peruvian Jungle - Karin Zbinden Gysin (Revue de Géographie Alpine)
The paper shows how an ethnic group in Pozuzo, an old colony founded by Tyrolean and German settlers in the Peruvian jungle, recreates an alpine way of life. This case study, which is based on evidence from the field in Pozuzo and in Tyrol, illustrates how cultural resources linked to ‘alpine’ ways of life are constructed and claimed within the multi-ethnic rural community of Pozuzo as well as in Tyrolean NGOs.